2012
DOI: 10.1002/ijc.27948
|View full text |Cite
|
Sign up to set email alerts
|

Activated leukocyte cell adhesion molecule soluble form: a potential biomarker of epithelial ovarian cancer is increased in type II tumors

Abstract: Activated leukocyte cell adhesion molecule (ALCAM) is involved in cell-cell interactions in cancer. Shedding of its ectodomain by the metalloprotease ADAM17/TACE generates a soluble form (sALCAM). Here, we show that serum sALCAM levels were significantly higher in epithelial ovarian cancer (EOC) (p < 0.005) than in controls. The performance of sALCAM as classifier, tested by receiver operating characteristic curve, resulted in an area under the curve (AUC) of 0.8067. Serum sALCAM levels showed direct correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 42 publications
(68 reference statements)
2
52
1
Order By: Relevance
“…Thus, serum levels of sCXCL16 might reflect tumour-associated ADAM activity. A similar association has previously been reported for ALCAM, an adhesion molecule also cleaved by ADAMs, with high serum sALCAM being predictive of poor survival (Carbotti et al , 2013). Indeed, in vitro inhibition of ADAM-10 and ADAM-17 enhanced CXCL16 expression on the membrane of (primary) OC cells and reduced sCXCL16 levels in culture supernatants.…”
Section: Discussionsupporting
confidence: 85%
“…Thus, serum levels of sCXCL16 might reflect tumour-associated ADAM activity. A similar association has previously been reported for ALCAM, an adhesion molecule also cleaved by ADAMs, with high serum sALCAM being predictive of poor survival (Carbotti et al , 2013). Indeed, in vitro inhibition of ADAM-10 and ADAM-17 enhanced CXCL16 expression on the membrane of (primary) OC cells and reduced sCXCL16 levels in culture supernatants.…”
Section: Discussionsupporting
confidence: 85%
“…4F). Shedding is likely to be universally present in solid tumors as it has been reported for colon cancer (10), ovarian cancer (11) and is easily detected in models of breast and prostate cancer (Suppl. Fig.…”
Section: Resultsmentioning
confidence: 93%
“…These studies suggest that ALCAM is shed by the tumor. Indeed, experimental models of ovarian cancers indicate elevated shedding of ALCAM specifically from the tumor (11). To determine if tumor-derived ALCAM is the source of elevated circulating ALCAM in prostate cancer we used species-specific antibodies to monitor circulating levels of both host (mouse) ALCAM and tumor (human) ALCAM longitudinally during orthotopic and subcutaneous growth of PC3 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum ALCAM levels have also been found to be significantly higher in EOC patients than in controls, and full-length transmembrane ALCAM was detected in exosomes extracted from EOC ascites samples. Studies have shown that ALCAM is a marker of EOC and correlates with more aggressive tumors [37]. …”
Section: Exosomes As Biomarkers Of Ocmentioning
confidence: 99%